FORMATION OF INTERNATIONAL NETWORKS ANTI-CORRUPTION EDUCATION BARISAN ANTIKORUPSI AHMAD DAHLAN (BAKAD-UAD) WITH ANGKATAN MAHASISWA ANTIRASUAH MALAYSIA (AMAR-UM) - Suyadi, Suyadi; Suyitno, Suyitno; Asmorojati, Anom Wahyu; Nusaibah, Afaf Wafiqoh; Andriani, Monik (Proceeding of International Conference on Islamic Education (ICIED); Vol 8 No 1 (2023): Proceeding of International Conference on Islamic Education (ICIED), 2023)
Corruption has become the enemy of all countries throughout the world, including Indonesia and Malaysia. Corruption eradication commissions in various countries have also collaborated to fight against corruption. In fact, in educational institutions, especially higher education, student groups have emerged as activists to prevent corruption. However, their movement is still local and partial, and has not yet formed an international network. This participatory action research is the first step in forming an international network of anti-corruption education in Indonesia and Malaysia. The results of this research and community service show evidence that there has been international collaboration between anti-corruption activist groups from Indonesia represented by the Barisan Antikorupsi Ahmad Dahlan (BAKAD) and Malaysian anti-corruption activists represented by the Malaysian Angkata Mahasiswa Antirasuah (AMAR) Universiti Malaya Malaysia. Both are committed to campaigning for anti-corruption prevention and strengthening cross-border integrity, especially in Indonesia and Malaysia.